(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the quality of life among parents of children with endocrine and metabolic diseases at the National Children’s Hospital in 2025. Participants and methods: The study was a descriptive cross-sectional on 315 parents of children with endocrine-metabolic diseases receiving treatment at the National Children’s Hospital from January 2025 to October 2025. Data was collected through direct interviews using a pre-designed questionnaire. The questionnaire was developed using the Beach Center’s 5-point FQoL. Results: The age group of 25–35 years accounted for the highest proportion (60.3%). Most parents lived in rural areas (75.2%). Families with a monthly income of ≥10 million VND accounted for 70.5%. Regarding educational level, 38.1% had lower secondary education or below, 24.4% had completed high school, and 37.5% had vocational or higher education. The most common occupation among parents was factory worker (32.4%). The majority of families had no history of hereditary diseases (94.3%), and most parents reported no disagreement regarding child-rearing practices (92.1%). The results showed that 63.5% of caregivers had a moderate level of quality of life, while 23.2% had good quality of life and 13.3% had poor quality of life. Conclusion: The quality of life among parents of children with endocrine-metabolic diseases is mainly average (63.5%), only 23.2% have a good quality of life, 13.3% have a low quality of life.